PREVALENSI SHIFT WORK SLEEP DISORDER PADA PEKERJA SHIFT MALAM DI BEBERAPA WARALABA DI DENPASAR SELATAN - Sari, Ida Ayu Candra; Purnawati, Susy (E-Jurnal Medika Udayana; Vol 6 No 7 (2017): E-Jurnal Medika Udayana, 2017)
The practice of shift work may cause risk factors for occupational health and safety, one of which is a circadian rhythm sleep disorder, called as shift work sleep disorder (SWSD). This study was conducted to find out the prevalence of SWSD with reference to night-shift workers in several outlets of convenience-store in south Denpasar. The study was conducted with cross-sectional and carried out on 84 samples by visiting each outlet, interviewing the employees, then asking them to fill the questionnaires. Research instrument used are the Epworth Sleepiness Scale (ESS) and the Insomnia Severity Index. Based on the Epworth Sleepiness Scale (ESS) questionnaire, 33 (39.3%) samples indicate clinical sleepiness and 51 (60.7%) samples did not show clinical sleepiness. On the other hand, by using the Insomnia Severity Index questionnaire, it is obtained moderate and severe insomnia as many as 27 (32.1%) samples. There are 14 samples indicate moderate insomnia and clinical sleep disorders. From the data obtained, thus the prevalence SWSD in several convenience-stores in South Denpasar is 46 (54.76%) and still requires certain concern and needs to implement sleep hygiene.